Students’ Mathematical Literacy Based On Visual Learning Style At Junior High School - Rizki, Lussy Midani; Kusumah, Yaya S.; Nurlaelah, Elah; Kusaka, Satoshi (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2023)
Mathematical literacy is the ability that students must have to face 21st-century challenges. Related to this, students have learning styles that influence the way students absorb and process information, namely: Visual, auditory, and kinesthetic. This research focuses on describing the mathematical literacy of junior high school students in each indicator classified from the visual learning style. This type of research is descriptive qualitative research. The steps in this study were to compile the learning style questionnaire sheet and mathematical literacy tests; ask students to fill out questionnaires and ability tests; and analyze the results of the learning style questionnaire and student answers on mathematical literacy tests. The subject of the study consisted of 49 class VIII junior high school students, and then the subject was reduced to 6 students. The findings show that: 1) Students with visual learning styles have mathematical literacy in the range of levels 1 to level 2; 2) Visual students have characteristics of answering briefly and difficulty choosing words. The results of this study can be used as consideration in determining treatment in the teaching and learning process in class to increase student mathematical literacy.